2011
DOI: 10.1016/j.eurpsy.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient mother-and-child postpartum psychiatric care: Factors associated with improvement in maternal mental health

Abstract: Most women improved significantly while under care in MBUs. Our results emphasize the importance of the type of disease but also its chronicity and the social integration when providing postpartum psychiatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 37 publications
(75 reference statements)
1
29
1
3
Order By: Relevance
“…Mothers in this study were more highly educated, relative to studies from other MBUs (Glangeaud‐Freudenthal et al., ; Salmon et al., ). Nearly all patients had some high‐school qualifications, and 53% had reached a tertiary level.…”
Section: Discussioncontrasting
confidence: 47%
“…Mothers in this study were more highly educated, relative to studies from other MBUs (Glangeaud‐Freudenthal et al., ; Salmon et al., ). Nearly all patients had some high‐school qualifications, and 53% had reached a tertiary level.…”
Section: Discussioncontrasting
confidence: 47%
“…A previous evaluation of the Parent Infant Program at Austin Hospital found that the average LOS was, on average, 23 days (Nair et al 2009). Although comparable with other Australian-based services (Buist et al 2004), it is significantly shorter than international MBUs particularly in UK (Elkin et al 2009) and France (Glangeaud-Freudenthal et al 2011) where the average LOS ranges from 8 to 11 weeks, respectively. This difference in LOS is an important one to consider, particularly in relation to the number of intervention sessions required to observe changes in mother-infant interaction/behavior.…”
Section: Discussionmentioning
confidence: 88%
“…In terms of the same datasets, Salmon and colleagues draw on the same UK Marcé database information Salmon et al 2004), and Howard and colleagues draw on a similar dataset to Salmon and colleagues but from slightly different Marcé entries (Howard et al 2003;Howard et al 2004). In France, Glangeaud-Freudenthal and colleagues draw on different samples but there was however some overlap of data from 13 French MBUs from the Marcé database, which was justified by the aims of the studies (Glangeaud-Freudenthal et al 2013;Glangeaud-Freudenthal et al 2011;Sutter-Dallay et al 2015). The data published in 2013 was added to the data from France published in 2011 (2001-2007; n=814), and the data from Belgium for the same period (2001-2007; n=1018) to allow more diversity in child status to study separation status at discharge from MBUs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Glangeaud-Freudenthal et al(2011) in their analysis of 869 women in 13 mother-baby units in France found that two thirds (69%) of the women were symptom-free or considerably improved by the time they were discharged, with this being higher for those with issues appearing (or reappearing) in the postpartum period compared to those with chronic mental illness. Whilst most of the studies in this theme of outcomes use quantitative methods to measure outcomes, they also acknowledge the need for more holistic approaches to the mother-infant relationship within the family and their broader social and economic milieu.…”
Section: [Insert Table 3 About Here]mentioning
confidence: 99%